Song as multimodal genre: a study in the cycle Volare (Per Musi, 2021)
The article aims to discuss ways in which poetry and music are interrelated in the construction of meanings and their deviations in the song genre; and to propose the understanding of song as a multimodal genre. Our objects of study are the reflections on the readings of Sônia Cintra's poems (1949-2018) for the creation of the song cycle Volare (2018), undertaken by Tadeu Taffarello, for low-pitched female voice and string orchestra. Adopting an interdisciplinary approach, song will be discussed as a multimodal genre and the creation contexts will be presented. Then, the songs from Volares will be grouped according to the thematic axes, demonstrating the orchestration and global structuring of the cycle. As a final result, it is intended that new approaches to the song genre may occur, based on an interdisciplinary perspective that seeks to open up new possibilities for scientific development and to collaborate for the understanding of the song genre and of current Brazilian music.